Blood substitutes : present and future perspectives - Tsuchida, E. (Eishun), 1930-2010 (Elsevier, 1998)
This book contains the selected papers presented at the seventh International Symposium on Blood Substitutes (7th ISBS) held at the International Conference Center of Waseda University in Tokyo on 7-10 September 1997. In keeping with the scientific design of the 7th ISBS Symposium, chapters have been carefully selected and organized to showcase the advancements in recent research. This book includes up-to-date clinical results of leading companies which are manufacturing hemoglobin-based or fluorocarbon-based blood substitutes, and covers issues of hemoglobin toxicity and side effects such as vasoconstriction in more detail using carefully designed in vivo and ex vivo techniques. This book is also a collection of various new types of red cell substitutes such as recombinant Hbs, recombinant albumine-lipidheme complex, modified red blood cells, and perfluorochemicals using material science and molecular engineering.